2020
DOI: 10.1155/2020/8869624
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Composition of Propolis and Its Efficacy in Maintaining Postharvest Storability of Fresh Fruits and Vegetables

Abstract: Propolis, also called “bee-glue,” is a natural resinous substance produced by honeybees from plant exudates, beeswax, and bee secretions in order to defend the hives. It has numerous phenolic compounds with more than 250 identified chemical compounds in its composition, which are also known to significantly vary according to the plant sources and season. Moreover, it has a long history in the traditional and scientific medicine as having antibacterial, anticancer, anti-inflammatory, anti-infective, and wound h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…In a study Petruzzi et al [61] reported that propolis delayed the fungal and bacterial growth. Similarly, Kahramanoglu et al [62] found that propolis is very effective in controlling pathogenic decay based on studies on its antimicrobial and fungicidal effects. Total yeast and mold counts of rainbow trout fillets coated with gelatin films during storage at 4 • C is shown in Figure 3.…”
Section: Changes In Microbiological Qualitymentioning
confidence: 99%
“…In a study Petruzzi et al [61] reported that propolis delayed the fungal and bacterial growth. Similarly, Kahramanoglu et al [62] found that propolis is very effective in controlling pathogenic decay based on studies on its antimicrobial and fungicidal effects. Total yeast and mold counts of rainbow trout fillets coated with gelatin films during storage at 4 • C is shown in Figure 3.…”
Section: Changes In Microbiological Qualitymentioning
confidence: 99%
“…Furthermore, there are two main mechanisms behind the antimicrobial activity of biomaterials, which are i) direct prevention of the pathogen growth with some biochemical reactions and ii) indirect prevention of pathogens by improving products tolerance to pathogens by induction of some enzymes. 17 On the other hand, there are some disadvantages, which make it challenging to develop and commercialize such practices. These are lack of knowledge, potential allergic reactions on different products, food safety issues, sensory implications and high costs.…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…Recently, Kahramanoglu et al (2020) have found that propolis can reduce the generation of reactive oxygen species (ROS) and lipid peroxidation as well as inhibit cell division thereby exhibiting a preservative effect. Its inhibitory effect is mainly attributed to inhibition of protein synthesis and certain functions of cell membranes (Kahramanoglu et al, 2020;Cruz et al, 2021). Correa et al (2019) indicated that propolis mainly inhibits aerobic microorganisms, while different bacterial species have different inhibitory concentrations.…”
Section: Propolismentioning
confidence: 99%
“…Correa et al (2019) indicated that propolis mainly inhibits aerobic microorganisms, while different bacterial species have different inhibitory concentrations. Furthermore, Kahramanoglu et al (2020) found that the propolis extract has a significant inhibitory effect on important genes in the biosynthetic pathway of aflatoxin at the concentration of 125 µg mL −1 . Kahramanoglu et al (2020) mentioned that the pretreatment with propolis can reduce the oxidase activity, catalase activity and superoxide dismutase activity in yeast, thereby inhibiting the growth of yeast.…”
Section: Propolismentioning
confidence: 99%